The dynamics of wild populations of Henosepilachna vigintioctomaculata Motch. (Coleoptera:Coccinellidae) in Primorsky Krai - N. V. Matsishina; P. V. Fisenko; M. V. Ermak; O. A. Sobko (Овощи России, 2023)
Relevance. Population dynamics (population waves) is an intrinsic quality of population systems. These fluctuations can be induced by various factors, e.g. environmental conditions and resource availability, elements of a food chain from the same or a higher level (competitors, parasites, predators), and diseases. Few researchers have addressed the issue of the population dynamics of Henosepilachna vigintioctomaculata in the Russian Far East. This paper investigates the reasons why the potato ladybird beetle became a pest of introduced cultivated plants.Materials and methods. To collect data on imagines, all research sites were examined at intervals of eight days during the entire period of the study. The examination of the research sites was conducted within one day. All the imagines taken from host plants were marked at the first encounter by puncturing their elytra with a sewing needle (0.4 mm in diameter) according to Hirano. The next generation of beetles was marked with nail polish (in two-three days after emergence) to avoid traumatizing the insects. At the second encounter, these beetles were also marked by puncturing their elytra with a needle. The methods implemented did not have an adverse effect on the survivability of the studied imagines. The beetles were released to the same plants where they had been taken from. The research data were analyzed by Jolly’s method.Results. Overwintered imagines appeared in the fields and began ovipositing at the end of May. The first generation of imagines appeared at the end of June – the begging of July. The second generation of imagines could be observed at the end of July – the beginning of August. A part of the imagines migrated to overwintering sites without ovipositing approximately at the end of August. The overwintered beetles were observed to emerge on the Mongolian oak Q uercus mongolica, the greater celandine Chelidonium majus, and the bird cherry Prunus padus. A typical primary biotope of the potato ladybird beetle was a potato field at the stage of vegetative growth (5-7 leaves) surrounded by the couch grass Elymus repens, the common dandelion Taraxacum officinale, and the perennial sow-thistle Sonchus arvensis. Marking the overwintered and new generations of imagines showed that the presence of the potato ladybird beetle in an ecosystem depended on agricultural and agrometeorological conditions.